Diagnostic yield and complication rate of transbronchial lung cryobiopsy using 1.1 mm probe in patients with interstitial lung disease - Margaret A. Kypreos; Kim C. Styrvoky; Steven Wu; Audra Schwalk; Traci N. Adams (PLoS ONE, 2026)
Background Widespread adoption of transbronchial lung cryobiopsy (TBLC) using a 1.9 or 2.4 mm touch cryoprobe in interstitial lung disease (ILD) has been limited by high bleeding risk. Recent studies have demonstrated that the 1.1 mm cryoprobe via conventional bronchoscope may achieve diagnostic yields comparable to larger probes while maintaining a favorable safety profile. Studies of the 1.1 mm touch cryoprobe in the diagnosis of ILD have been flawed and conflicting. Aim The aim of this study is to describe the complication rate, diagnostic yield, and factors that increase diagnostic yield of TBLC using a 1.1 mm touch cryoprobe in patients with ILD. Methods The retrospective cohort study included patients that were prospectively identified in the ILD clinic registry at University of Texas Southwestern Medical Center (UTSW) who underwent TBLC from 2022–2026. Procedural characteristics were recorded. Patients were assigned a pre-TBLC, post-TBLC, and final diagnosis. Results This study demonstrates that TBLC using a 1.1 mm probe added to BAL significantly increases diagnostic yield with an 11% risk of pneumothorax and a 6.5% risk of bleeding. The combination of BAL and TBLC was diagnostic in 27 (43.5%) of patients and led to a change in diagnosis in 27 (43.5%) of patients. The number of TBLC samples taken is associated with a higher diagnostic yield. Conclusion The diagnostic yield and complication rates of the 1.1 mm touch probe in our study are higher than previously reported studies with TBBx but lower than 1.9 and 2.4 mm touch probes, though there was no direct comparison group in our study. To increase yield of the procedure, multiple lobes should be biopsied and more samples taken.